PERANCANGAN MEDIA EDUKASI MENGGUNAKAN AUGMENTED REALITY MENGENAI PAKAIAN TARI BEDHAYA SUKAHARJA - Mataram, Sayid; Nanprahita, Lovely Ayunda (LPPM Institut Teknologi Telkom Purwokerto, 2024)
The preservation of culture in Indonesia, exemplified through its diversity in each region, particularly in traditional dances such as Tari Bedhaya Sukaharja, faces significant challenges in terms of understanding and preservation by the millennial generation. Their role is crucial as agents of preservation and bearers of local values. To engage the millennial generation, augmented reality (AR) technology is considered a fitting solution. AR is an innovative and interactive tool that can help millennials understand and preserve cultural heritage in an engaging and relevant way. This study employs the structured waterfall method, which includes steps for planning, design, development, testing, evaluation, and implementation. The study sample was chosen at random, with the goal of laying a solid foundation for understanding the impact of AR technology in enhancing the understanding and awareness of the millennial generation ages 12-18 regarding the preservation of Indonesian cultural heritage, specifically in the context of Tari Bedhaya Sukaharja.